2005
DOI: 10.1081/iph-200067950
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of TH2-Type Immune Response-Mediated Allergic Diarrhea Following Oral Administration of Traditional Korean Medicine:Atractylodes MacrocephalaKoidz

Abstract: Atractylodes macrocephala Koidz (AMK) is well-known as a digestive and tonic material and is widely used in traditional Korean herbal medicines. Previously, we found that protein samples obtained from the medicines could induce a preferential stimulation of type 1, rather than type 2, helper T lymphocytes (Th) immune responses in vitro. Since immune response induction is controlled by the balanced activation between Th1- and Th2-type immune responses, we tested to see whether or not the AMK protein sample coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Each of them or their components has already been reported to have an effect on the symptoms of allergy. Mice administered with Atractylodes lancea D.C extract experienced suppression of OVA‐mediated allergic diarrhea by preferential stimulation of Th1‐type immune responses [34] . Atractylenolide III, a component of Atractylodes lancea D.C, significantly decreases histamine release increased by PMA plus A23187 in HMC‐1 cells [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Each of them or their components has already been reported to have an effect on the symptoms of allergy. Mice administered with Atractylodes lancea D.C extract experienced suppression of OVA‐mediated allergic diarrhea by preferential stimulation of Th1‐type immune responses [34] . Atractylenolide III, a component of Atractylodes lancea D.C, significantly decreases histamine release increased by PMA plus A23187 in HMC‐1 cells [35] .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite evidence of systemic Th2 immunity in cutaneous-and respiratory mucosal-sensitized mice, these mice were unable to develop GI manifestations upon intragastric Ag challenge. Previous studies have demonstrated that oral Aginduced diarrhea and allergic GI responses in mice are dependent on the induction of Th2 immunity including GI inflammation mediated by IgE-primed mast cells, eosinophils, and CD4 ϩ Th2 cells (25,35,36). In those studies, disease-positive animals had also been sensitized systemically although the precise involvement of specific LNs during sensitization was not examined (25).…”
Section: Discussionmentioning
confidence: 99%
“…C. foetida has versatile medical applications and is prescribed to ease uncomfortable feelings or medical symptoms caused by hot flashes, diabetes, inflammatory, HIV or malaria infection, osteoporosis, and vasoactive complications (Li and Yu, 2006). Finally, the glycoproteins from A. macrocephala have been proven to have stimulatory effects on mouse splenocytes (Lee et al, 2007), and oral administration of its protein extract preferentially stimulated the Th1 immune responses that suppressed ovalbumin-mediated allergic diarrhea (Kim et al, 2005). Summing up the reports described above leads to the conclusion that every herbal component in CUC has an immunomodulative effect, and administering the herbal medicinal formula should benefit patients' general immunity in protecting against or curing infections, tumors, diabetes, and the immune-related diseases.…”
Section: Trem-1 Tnf-mentioning
confidence: 98%